2022
DOI: 10.1515/mt-2021-2064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene nanoplatelets on mechanical and impact properties of an aramid/glass-reinforced epoxy composite

Abstract: This study aims to characterize and evaluate the effects of graphene nanoplatelets (GnPs) added to the epoxy matrix and the fiber stacking sequence on the mechanical and impact responses of carbon/aramid hybrid composites. For this purpose, Aramid/Glass/Aramid and Glass/Aramid/Glass stacking sequences as well as full Aramid and Glass fiber configurations were used in an epoxy matrix with various contents (0.1, 0.25, 0.5 wt%) of GnPs. Tensile and flexural tests were conducted per mechanical characterization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to the images, it can be said that the fiber surfaces of the samples which have a high buckling performance were seen as rougher than the pure ones and showed a better fiber/matrix bonding. [ 49 ] This demonstrated that NC particles contributing to load transferring capability from matrix to fiber reinforcements increased the buckling resistance. This situation improved the buckling performance of the samples particularly seen in 0.5, 1, and 1.5 wt% compared with pure samples.…”
Section: Resultsmentioning
confidence: 99%
“…According to the images, it can be said that the fiber surfaces of the samples which have a high buckling performance were seen as rougher than the pure ones and showed a better fiber/matrix bonding. [ 49 ] This demonstrated that NC particles contributing to load transferring capability from matrix to fiber reinforcements increased the buckling resistance. This situation improved the buckling performance of the samples particularly seen in 0.5, 1, and 1.5 wt% compared with pure samples.…”
Section: Resultsmentioning
confidence: 99%
“…At 0.1 wt%, the GnPs-matrix resin-fiber interactions resulted in a significant improvement in mechanical and impact properties, indicating a better load transfer. 23 According to the outcome, 24 graphene nanoplatelets had a significant influence on the impact and mechanical properties of glass/aramid-reinforced epoxy composites. Among the aramid fiber locations, absorbing energy, peak load values, and displacement were significantly affected.…”
Section: Introductionmentioning
confidence: 99%
“…In a search in which Kevlar fiber and sisal fiber formed a hybrid composite, it was found that maximum mechanical properties were obtained when the nano silica additive to the polyester resin was 4%, and it was understood that increasing the nano silica ratio more than 4% had a negative effect on the mechanical properties [21]. In the study of Dogan et al [22], they found that the absorbed energy and deformation amounts of graphene nanoplatelets added at different rates to the hybrid structure consisting of Aramid fiber and carbon fiber also had a significant effect. It was stated that 0.1% and 0.25% by weight nanoparticles added to the resin created the best effect on the structures.…”
Section: Introductionmentioning
confidence: 99%